‘We are not our parents’: beyond political transition : historical failings, present angst and future yearnings of South African youth - Maringira, Godfrey (International journal of transitional justice, 2022)
The story of South Africa’s liberation struggle, from apartheid to constitutional democracy, is writ large with in-depth contributions from young people. Despite their historical involvement, young people have been noticeably absent from the transitional processes ushering in South Africa’s postapartheid dispensation. Their absence has created a crisis of legitimacy, particularly among those disillusioned young people who are unsentimental about the transition and who are growing increasingly impatient and frustrated with the slow pace of transformation in postapartheid South Africa, in particular within institutions of higher learning. Internationally, South Africa is widely considered as a role model for transitional justice, largely due to its peaceful transference of power from minority rule to the current democratic system. Domestically, however, South Africa’s transition has come under fire for prioritizing reconciliation without simultaneously addressing the social, institutional, political and economic injustices of the past. This article uses the ‘#FeesMustFall’ student protests that swept across South African universities from 2015 to 2017 as a case study for critically discussing whether young people feel South Africa’s transition has been transformative in terms of addressing its colonial and apartheid legacy. Conceptually, the article is rooted within institutional and decolonial transformative justice literature that identifies how the failure of transitional processes to address colonial civil-political and socioeconomic rights can lead to violence. It is argued that the #FeesMustFall protests represented a call for inclusive transitional justice processes that address past inequalities which continue to manifest in the present, including unequal access to free, quality and decolonized education.